Owstonia aurora (Perciformes: Cepolidae: Owstoniinae), a new bandfish from the Philippines - Liao, Yun-Chih; Reyes , Rodolfo B. Jr.; Shao, Kwang-Tsao (Zootaxa, 2022)
Owstonia aurora sp. nov. is described on the base of three specimens (69.8–88.0 mm in standard length) collected off East Luzon during the “Aurora 2007” Philippine Expedition. The new species differs from its congeners by the following combination of characters: dorsal-fin elements III, 21; anal-fin elements I, 14; gill rakers on first arch 35–38; cheek with 80–86 scales in 7–8 rows; lateral line without branch, not forming loop in front of dorsal-fin, ending below 17th to 22th dorsal-fin soft rays; oblique body scale rows in mid-lateral series 54–58; lower margin of preopercle rounded; prominent black blotch on anterior dorsal-fin membrane, and extend downward to dorsal-fin base, remaining membrane of dorsal, anal, and caudal fins red with white margins and bases, distinct white stripes on mid dorsal and caudal fin membranes; membranes between maxillary and premaxillary with discontinuous black stripes or patches.